Midwifery practice during birth: Ritual companionship. Issue 3 (June 2016) - Reed, Rachel; Rowe, Jennifer; Barnes, Margaret
Abstract: Background: There is an expectation that midwifery practice is woman centred and promotes physiology. In addition, midwives must assess the wellbeing of mother and baby, and monitor the progress of labour. It is important to understand how midwifery actions and interactions influence the birth experience for women. Aim: The aim of this study was to explore midwifery practice during physiological birth from the perspective of both midwives and mothers. Method: A narrative inquiry involving face-to-face in-depth interviews was used to gather data. The participants were 10 midwives and 10 women who had recently attended or experienced an uncomplicated physiological birth. Data was analysed to identify themes occurring across the narratives. Findings: Two types of midwifery practice were identified from the data: rites of passage and rites of protection. Rites of passage were synergistic with women's needs during birth and involved managing distractions and reflecting internal wisdom. Rites of protection involved performing clinical assessments to determine wellbeing and labour progress. These practices could contradict the rites of passage by disrupting aloneness and reinforcing external wisdom. Conclusion: Midwives performed two types of practices which intersected with women's experience of birth in differing and contested ways. Conceptualising the role of the midwife as a 'ritual companion' and actions and words as rituals enables a deeper exploration of the values transmitted and reflected by midwifery practice. This study contributes to a discourse about midwifery practice during birth, women's experience of birth, and the influence of the institution on the nature of mother–midwife relationship.